THERAPEUTIC POTENTIAL OF PLANT-DERIVED OLIGOSTILBENES AND STILBENE GLYCOSIDES - MAJEE, SUTAPA BISWAS; ASH, DIPANJANA; AVLANI, DHRUTI; BISWAS, GOPA ROY (International Journal of Current Pharmaceutical Research, 2020)
Stilbenoids constitute a major class of plant-derived secondary metabolites occurring in abundance across several families and are well-known for their nutritional and health-promoting benefits. Several investigations have established their therapeutic potential in the management of different types of cancer, neuroinflammation, arthritis, disorders in lipid metabolism, microbial infection etc. Studies on resveratrol monomer, oxyresveratrol, their synthetic analogs, piceatannol, pterostilbene can be found in the literature. But a collective and comprehensive review on chemistry, pharmacological effects, structure-activity relationship and pharmacokinetics of plant-derived oligostilbenes and stilbene glycosides is missing. These phytochemicals are generally characterised by poor oral bioavailability due to extensive first-pass metabolism and conjugation. The present chapter aims to fill up these lacunae and also focuses on further studies that can be performed in the future to translate these immensely potential secondary metabolites into human clinical setting from cell culture and animal studies at the preclinical level for effective therapeutic intervention of various pathological conditions.